Deep brain stimulation of the ventrointermediate nucleus of the thalamus to treat essential tremor improves motor sequence learning. Issue 15 (6th July 2022) - Terzic, Laila; Voegtle, Angela; Farahat, Amr; Hartong, Nanna; Galazky, Imke; Nasuto, Slawomir J.; Andrade, Adriano de Oliveira; Knight, Robert T.; Ivry, Richard B.; Voges, Jürgen; Buentjen, Lars; Sweeney‐Reed, Catherine M.
Abstract: The network of brain structures engaged in motor sequence learning comprises the same structures as those involved in tremor, including basal ganglia, cerebellum, thalamus, and motor cortex. Deep brain stimulation (DBS) of the ventrointermediate nucleus of the thalamus (VIM) reduces tremor, but the effects on motor sequence learning are unknown. We investigated whether VIM stimulation has an impact on motor sequence learning and hypothesized that stimulation effects depend on the laterality of electrode location. Twenty patients (age: 38–81 years; 12 female) with VIM electrodes implanted to treat essential tremor (ET) successfully performed a serial reaction time task, varying whether the stimuli followed a repeating pattern or were selected at random, during which VIM‐DBS was either on or off. Analyses of variance were applied to evaluate motor sequence learning performance according to reaction times (RTs) and accuracy. An interaction was observed between whether the sequence was repeated or random and whether VIM‐DBS was on or off ( F [1, 18] = 7.89, p = .012). Motor sequence learning, reflected by reduced RTs for repeated sequences, was greater with DBS on than off ( T [19] = 2.34, p = .031). Stimulation location correlated with the degree of motor learning, with greater motor learning when stimulation targeted the lateral VIM ( n = 23, ρ = 0.46; p = .027). These results demonstrate the beneficial effects of VIM‐DBS on motor sequence learning in ET patients, particularly with lateral VIM electrode location, and provide evidence for a role for the VIM in motor sequence learning. Abstract : Motor sequence learning enables activities like playing the piano without conscious thought. Tremor engages similar brain structures to those supporting motor learning. Stimulation of the ventrointermediate nucleus of the thalamus is effective in treating tremor, and we demonstrate that it also improves motor sequence learning, with greater performance modulation when the stimulating electrode is more lateral.